Perancangan Sistem Pemesanan Tiket Bus Online Berbasis Web - Robby Rachmatullah (APMMI - Asosiasi Profesi Multimedia Indonesia, 2014)
Abstract - Current usage of Internet services as a means to obtain information more widely used. Because of extensive coverage, the Internet is ideal when used as a promotional tool and a means to publish the information. The purpose of making this web program is to promote the company as well as providing services to customers regarding ticket booking on-line. Internet is a medium that is very potential to develop an information system that is dynamic and wide-ranging, with any information on the internet can be obtained easily and quickly. Based on the various facilities and their role of being owned by the internet then developed a